Effects of aprepitant on post-operative nausea and vomiting in patients with congenital heart disease undergoing cardiac surgery or catheterization procedures: a retrospective study with subjects as their own historical control - Belk, John W.; Twite, Mark D.; Klockau, Katherine S.; Silveira, Lori J.; Clopton, Rachel G. (Frontiers in Anesthesiology, 2023)
Introduction For patients undergoing cardiac surgery and catheterization procedures, severe post-operative nausea and vomiting (PONV) can occur despite standard anti-emetic interventions. Aprepitant, a neurokinin-1 (NK-1) receptor blocker, is safe and effective at preventing PONV resistant to standard therapies. Methods Patients with a history of severe PONV presenting for cardiac surgery or catheterization procedures from January 1, 2018 to January 6, 2021 were identified. After pharmacist approval, patients received aprepitant pre-operatively (Dose: 80 mg for weight >50 kg, 40 mg for weight 30–50 kg). A retrospective chart review was performed. Primary outcomes of the incidence of PONV and PONV-related complications were evaluated. Results Seventeen patients were included with a mean age of 16.0 years at the time of their initial procedure, which acted as the “control” procedure, and 17.5 years when they received aprepitant. After the control procedure 64.7% of patients required rescue anti-emetics. When this group of patients received aprepitant pre-operatively at their subsequent procedure, only 17.6% required rescue medication (p = 0.005). Similarly, 64.7% of patients suffered at least one PONV-related complication after the control procedure. With aprepitant use pre-operatively, 5.9% of the same patients experienced a PONV-complication (p = 0.0003). Specifically, unplanned ICU admission due to severe PONV after catheterization procedures decreased from 55.6% (5/9) in the control group to 0 after these patients were treated pre-emptively with aprepitant (p = 0.01). For surgical patients, there were significant decreases in PONV-related complications including delayed oral intake and delayed ambulation (p = 0.04) in the aprepitant group compared to the control group. Discussion This small, retrospective study supports the conclusion that preoperative aprepitant administration in patients undergoing cardiac catheterization or cardiac surgery with a history of congenital heart disease and severe PONV significantly reduces the incidence of PONV and PONV-related complications. Decreasing these complications will likely improve the surgical experience for patients and families while also decreasing hospital costs and improving efficiency.